KHANATE OF KOKAN DURING THE TIME OF OLIM KHAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the acceptance of Kokan Khan Olimkhan to the throne of Kokan, the future name of Kokan Khanate, the state management and various processes he led in the country, the important events that took place in his time, are discussed will be lit